Hospitalization due to mental and behavioral disorders caused by use of alcohol and psychoactive substances among older adults and elderly people in Brazil: a cross-sectional study - Afonso, Pedro Paulo Luciano; Afonso, Mariana Luciano; Barbosa, Gabriela Rodrigues; Justo, Alberto Fernando Oliveira (São Paulo Medical Journal, 2022)
BACKGROUND: It has been estimated that 17% of individuals aged 50 years or older suffer from addiction to legal or illegal drugs. Use of alcohol and psychoactive substances has been correlated with several diseases, e.g. psychiatric conditions and cardiovascular and sexual dysfunctions. OBJECTIVE: To discuss the Brazilian profile of mental and behavioral disorders caused by use of alcohol and psychoactive substances among older adults and elderly people, over the period from 2008 to 2019. DESIGN AND SETTING: Cross-sectional study conducted among Brazilians aged 50 years or older. METHODS: Hospitalization due to mental and behavioral disorders caused by use of alcohol and psychoactive substances was assessed through data obtained from the National Health System Department of Informatics (Departamento de Informática do Sistema Único de Saúde, DATASUS). RESULTS: Decreasing and steady trends of hospitalization due to mental and behavioral disorders caused by use of alcohol among both men and women at all ages were observed. Similar trends were reported for all age ranges among men and women aged 60 years and older. In contrast, a slight increase was seen among women aged 50 to 59 years. CONCLUSION: These data are crucial for qualifying mental healthcare for older adults and elderly people and for planning mental health services.